2008
DOI: 10.1007/s10522-008-9193-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hsc70 as target for AGE modification in senescent human fibroblasts

Abstract: Cellular senescence is known as a potent mechanism of tumor suppression, and cellular senescence in vitro also reflects at least some features of aging in vivo. The Free Radical Theory of aging suggests that reactive oxygen species are important causative agents of aging and cellular senescence. Besides damage of nucleic acids and lipids, also oxidative modifications of proteins have been described as potential causative events in the senescence response. However, the identity of protein targets for post-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
1
4
1
Order By: Relevance
“…Gutsmann-Conrad et al have shown that the expression of HSP70 also decreased with senescence in IMR-90 lung fibroblasts during in vitro studies of cells from young or old subjects [56] and in senescent human fibroblasts [57]. In our analyses, we found a significantly reduced expression of HSP70 protein 6.…”
Section: Discussionsupporting
confidence: 61%
“…Gutsmann-Conrad et al have shown that the expression of HSP70 also decreased with senescence in IMR-90 lung fibroblasts during in vitro studies of cells from young or old subjects [56] and in senescent human fibroblasts [57]. In our analyses, we found a significantly reduced expression of HSP70 protein 6.…”
Section: Discussionsupporting
confidence: 61%
“…, 2006). In addition, it was identified as target for AGE modification in human senescent dermal fibroblasts (Unterluggauer et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Formation of AGE on proteins is found in many tissues and is thought to contribute to a variety of age‐associated diseases (Reddy & Beyaz, 2006). Interestingly, Hsc 70 has been recently shown to be AGE‐modified in senescent human dermal fibroblasts (Unterluggauer et al. , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Detection of protein carbonylation was performed as described elsewhere (59). For analysis of PTEN oxidation, lysates were prepared in the presence of 10 mM N-ethylmaleimide to prevent cysteine oxidation during lysis.…”
Section: Western Blotting and Immunohistochemistrymentioning
confidence: 99%